2020
DOI: 10.3389/fped.2020.00119
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Prevention of Severe Necrotizing Enterocolitis: Experience of New Zealand Neonatal Intensive Care Units

Abstract: Introduction: Necrotizing enterocolitis (NEC) affects mainly preterm infants, has a multifactorial etiology and is associated with intestinal dysbiosis and disordered immunity. Use of probiotics for prophylaxis is beneficial with studies indicating reduction in NEC ≥ stage 2, late onset sepsis (LOS) and mortality. However, not all studies have shown a reduction, there are questions regarding which probiotic to use, whether infants <1,000 g benefit and the risk of probiotic sepsis. All neonatal intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…32 A recent large ret rospective study of neonatal units in New Zealand also found a significant decrease in lateonset sepsis and necro tizing enterocolitis from 2.6% to 1.8% (OR 0.62, 95% CI 0.41-0.94) despite a low baseline incidence of necrotizing enterocolitis. 33 Although breast milk was used more at onset of feeding in their probiotic group, multivariate logistic regression showed minimal effect by confounders. At the BCWH NICU, the use of maternal and donor breast milk did not change significantly before and after probiotic introduction (88% v. 92%, p = 0.16).…”
Section: E647mentioning
confidence: 94%
“…32 A recent large ret rospective study of neonatal units in New Zealand also found a significant decrease in lateonset sepsis and necro tizing enterocolitis from 2.6% to 1.8% (OR 0.62, 95% CI 0.41-0.94) despite a low baseline incidence of necrotizing enterocolitis. 33 Although breast milk was used more at onset of feeding in their probiotic group, multivariate logistic regression showed minimal effect by confounders. At the BCWH NICU, the use of maternal and donor breast milk did not change significantly before and after probiotic introduction (88% v. 92%, p = 0.16).…”
Section: E647mentioning
confidence: 94%
“…Necrotizing enterocolitis (NEC) is an inflammatory disease that affects premature infants and is characterized by necrosis of the distal small intestine and colon (Meyer et al 2020 ). Short-chain fatty acids produced by Bifidobacterium infantis demonstrated anti-inflammatory activities in mature enterocytes and immunocytes (Zheng et al 2020 ) which suggests the symbiotic action of breast milk and probiotics in preventing necrotizing enterocolitis (Repa et al 2015 ).…”
Section: Immunomodulatory Activity Of Bacterial Extractsmentioning
confidence: 99%
“…Both approaches seem to restore the microbiome, it has a similar composition to that of naturally delivered newborns [ 253 , 254 , 255 ]. Finally, using probiotics in the neonatal period apparently diminishes the incidence of NEC [ 256 , 257 ]; however, studies with long-term follow-up and a significant number of participants are needed.…”
Section: Opportunities To Modulate Newborn Microbiotamentioning
confidence: 99%